2015
DOI: 10.1089/dia.2014.0304
|View full text |Cite
|
Sign up to set email alerts
|

The Michigan Model for Coronary Heart Disease in Type 2 Diabetes: Development and Validation

Abstract: Objectives: The aim of this study was to develop and validate a computer simulation model for coronary heart disease (CHD) in type 2 diabetes mellitus (T2DM) that reflects current medical and surgical treatments. Research Design and Methods: We modified the structure of the CHD submodel in the Michigan Model for Diabetes to allow for revascularization procedures before and after first myocardial infarction, for repeat myocardial infarctions and repeat revascularization procedures, and for congestive heart fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…In comparison with other T2DM models, the MAPE measure for PREDICT-DM versus ACCORD endpoints was 22% (combined over intensive and standard control arms), lower than the 33% error reported by one model 58 and the 83% error of another model. 67 Similarly, the MAPE measure for PREDICT-DM compared with VADT endpoints was 24%, lower than the 45% reported elsewhere 58 and similar to the 24% error of a previous model. 67 We could not find validation results against Look AHEAD for other T2DM models.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In comparison with other T2DM models, the MAPE measure for PREDICT-DM versus ACCORD endpoints was 22% (combined over intensive and standard control arms), lower than the 33% error reported by one model 58 and the 83% error of another model. 67 Similarly, the MAPE measure for PREDICT-DM compared with VADT endpoints was 24%, lower than the 45% reported elsewhere 58 and similar to the 24% error of a previous model. 67 We could not find validation results against Look AHEAD for other T2DM models.…”
Section: Discussionsupporting
confidence: 51%
“…67 Similarly, the MAPE measure for PREDICT-DM compared with VADT endpoints was 24%, lower than the 45% reported elsewhere 58 and similar to the 24% error of a previous model. 67 We could not find validation results against Look AHEAD for other T2DM models. Our ICC values were ‡89% for different outcomes; an ICC above 90% (70%) is often regarded as excellent (good) agreement between model and trial.…”
Section: Discussionsupporting
confidence: 51%
“…Of those, 3383 records were excluded based on their title and/or abstract. Sixty-eight articles were screened in full-text and 15 articles were included after applying the inclusion and exclusion criteria [2, 416, 24]. The resulting PRISMA diagram can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 15 included articles, the majority of the studies ( n = 10) were model-based cost-effectiveness analysis studies, which reported some limited amount of verification efforts [716]. The reporting of the verification efforts in none of these studies was systematic.…”
Section: Resultsmentioning
confidence: 99%
“…Different treatment and management strategies are evaluated through their impact on risk factor levels. Elements of UKPDS‐OM1 and UKPDS‐OM2 have been widely used in many other prediabetes and diabetes simulation models 13–18 …”
Section: Methodsmentioning
confidence: 99%